Acute and long-term responses to different rest intervals in low-load resistance training - Fink, J. E.; Schoenfeld, B. J.; Kikuchi, N.; Nakazato, K (International Journal of Sports Medicine, 2017)
We investigated the effects of low-load resistance training to failure performed with different rest intervals on acute hormonal responses and long-term muscle and strength gains. In the acute study, 14 participants were assigned to either a short rest (S, 30 s) or long rest (L, 150 s) protocol at 40% one-repetition maximum. Blood samples were taken before and after the workout. Both groups showed significant (p<0.05) increases in growth hormone and insulin-like growth factor 1 immediately post-workout. In the longitudinal study, the same protocol as in the acute study was performed 2 times per week for 8 weeks by 21 volunteers. Both groups showed significant increases in triceps (S: 9.8±8.8%, L: 10.6±9.6%, p<0.05) and thigh (S: 5.7±4.7%, L: 8.3±6.4%, p<0.05) cross-sectional area. One-repetition maximum also significantly increased for the bench press (S: 9.9±6.9%, L: 6.5±5.8%, p<0.05) and squat (S: 5.2±6.7%, L: 5.4±3.5%, p<0.05). In conclusion, our results suggest that acute hormonal responses, as well as chronic changes in muscle hypertrophy and strength in low-load training to failure are independent of the rest interval length.